Wound healing protects against chemotherapy-induced alopecia in young rats via up-regulating interleukin-1β-mediated signaling - Olivera Stojadinovic (Heliyon, 2017)
Wound healing is a complex process regulated by various cell types and a plethora of mediators. While interactions between wounded skin and the hair follicles (HFs) could induce HF neogenesis or promote wound healing, it remains unknown whether the wound healing-associated signaling milieu can be manipulated to protect against alopecia, such as chemotherapy-induced alopecia (CIA). Utilizing a well-established neonatal rat model of CIA, we show here that skin wounding protects from alopecia caused by several clinically relevant chemotherapeutic regimens, and that protection is dependent on the time of wounding and hair cycle stage. Gene expression profiling unveiled a significant increase in interleukin-1 beta (IL-1β) mediated signaling by skin wounding. Subsequently, we showed that IL-1β is sufficient and indispensable for mediating the CIA-protective effect. Administration of IL-1β alone to unwounded rats exhibited local CIA protection while IL-1β neutralization abrogated CIA protection by wounding. Mechanistically, IL-1β retarded postnatal HF morphogenesis, making HFs at the wound sites or IL-1β treated areas damage-resistant while the rats developed total alopecia elsewhere. We conclude that wound healing switches the cutaneous cytokine milieu to an IL-1β-dominated state thus retarding HF growth progression and rendering the HFs resistant to chemotherapy agents. In the future, manipulation of HF progression through interfering with the IL-1β signaling milieu may provide therapeutic benefits to a variety of conditions, from prevention of CIA to inhibition of hair growth and treatment of hirsutism.